MIDDLE TRIASSIC CONTINENTAL PALYNOLOGICAL ASSEMBLAGES OF SAN RAFAEL DEPOCENTER, CENTRAL-WESTERN ARGENTINA (Ameghiniana, 2023)
This contribution presents a comprehensive study of the unique and rich terrestrial Middle Triassic palynofloras recovered from the Quebrada de los Fósiles Formation, lower unit of the Puesto Viejo Group, San Rafael depocenter, Mendoza Province, Argentina. The palynoflora were recorded at two sections of the unit (Quebrada de los Fósiles creek and Río Seco de la Quebrada creek) yield diverse and well-preserved spores, pollen, freshwater algae and fungal associations. Herein, 259 spore-pollen species are described and/or illustrated from which eight are new: Baculatisporites magnus sp. nov., Carnisporites microspinous sp. nov., Leschikisporis variabilis sp. nov., Neoraistrickia stricta sp. nov., Limatulasporites rugulatus sp. nov., Aratrisporites circularis sp. nov., Protohaploxypinus bonapartei sp. nov. and P. diazii sp. nov. The following new combinations are proposed: Brevitriletes decorus, B. pamelae, B. sandrae, Cuneatisporites cacheutensis, C. salujhai and Pityosporites thoracatus. A new emendation for Alisporites cymbatus is instituted, and A. libyaensis nom nov.. is a new name to replace A. plicatus. These microfloras present a varied parental vegetation, containing high proportions of spores from Pleuromeiales, Equisetales, Marattiales, and Corytopermales pollen. In smaller proportions, the grains of Araucariaceae, Cupressaceae, Voltziales, Cordaitales, Gnetales, Ginkgoales/Cycadales are recorded. Zygospores of Chlorophyticalgae and Fungi are also recordered in these assemblages. The microflora of the Quebrada de los Fósiles Formation is clearly distinctive, quantitatively and qualitatively, from the rest of the Triassic microfloras, exhibiting the highest similarities in its composition with the associations of the La Veteada (Early Triassic, Olenekian) and Cerro de Las Cabras (Late Anisian–Early Ladinian) formations.